Initial Stress Hyperglycemia Is Associated With Malignant Cerebral Edema, Hemorrhage, and Poor Functional Outcome After Mechanical Thrombectomy. Issue 1 (January 2022) - Cannarsa, Gregory J.; Wessell, Aaron P.; Chryssikos, Timothy; Stokum, Jesse A.; Kim, Kevin; De Paula Carvalho, Helio; Miller, Timothy R.; Morris, Nicholas; Badjatia, Neeraj; Chaturvedi, Seemant; Gandhi, Dheeraj; Simard, J. Marc; et al.
Abstract : BACKGROUND: Malignant cerebral edema (MCE) and intracranial hemorrhage (ICH) are associated with poor neurological outcomes despite revascularization after mechanical thrombectomy (MT). The factors associated with the development of MCE and ICH after MT are not well understood. OBJECTIVE: To determine periprocedural factors associated with MCE, ICH, and poor functional outcome. METHODS: We retrospectively analyzed anterior cerebral circulation large vessel occlusion cases that underwent MT from 2012 to 2019 at a single Comprehensive Stroke Center. Multivariate logistic regression analyses were performed to determine significant predictors of MCE, ICH, and poor functional outcome (modified Rankin Scale, 3-6) at 90 d. RESULTS: Four hundred patients were included. Significant independent predictors of MCE after MT included initial stress glucose ratio (iSGR) (odds ratio [OR], 14.26; 95% CI, 3.82-53.26; P < .001), National Institutes of Health Stroke Scale (NIHSS) (OR, 1.10; 95% CI, 1.03-1.18; P = .008), internal carotid artery compared with M1 or M2 occlusion, and absence of successful revascularization (OR, 0.16; 95% CI, 0.06-0.44; P < .001). Significant independent predictors of poor functional outcome included MCE (OR, 7.47; 95% CI, 2.20-25.37; P = .001), iSGR (OR, 5.15; 95% CI, 1.82-14.53; P = .002), ICH (OR, 4.77; 95% CI, 1.20-18.69; P = .024), NIHSS (OR, 1.10; 95% CI, 1.05-1.16; P < .001), age (OR, 1.04; 95% CI, 1.03-1.07; P < .001), and thrombolysis in cerebral infarction 2C/3 recanalization (OR, 0.12; 95% CI, 0.05-0.29; P < .001). CONCLUSION: Elevated iSGR significantly increases the risk of MCE and ICH and is an independent predictor of poor functional outcome. Thrombolysis in cerebral infarction 2C/3 revascularization is associated with reduced risk of MCE, ICH, and poor functional outcome. Whether stress hyperglycemia represents a modifiable risk factor is uncertain, and further investigation is warranted.